2009
DOI: 10.1007/s12020-009-9228-5
|View full text |Cite
|
Sign up to set email alerts
|

FABP4: a novel candidate gene for polycystic ovary syndrome

Abstract: The present study is the first to establish an association between FABP4 gene polymorphisms and the development of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…144 In an independent study, the same variant in the FABP4 promoter resulted in reduced FABP4 expression and was associated with decreased total cholesterol levels and reduced risk of myocardial infarction in patients with advanced atherosclerosis. 145 Moreover, in other small studies an association between FABP4 polymorphisms, plasma levels of FABP4 and metabolic outcome in polycystic ovary syndrome, 146 and obstructive sleep apnoea 147 have been found. Consequently, overwhelming biochemical and genetic evidence demonstrates an important correlation between circulating levels of FABP4 and metabolic disease, which raises the possibility that targeting this form of the molecule might be a useful therapeutic intervention.…”
Section: Circulating Fabp4 and Metabolic Pathologymentioning
confidence: 89%
“…144 In an independent study, the same variant in the FABP4 promoter resulted in reduced FABP4 expression and was associated with decreased total cholesterol levels and reduced risk of myocardial infarction in patients with advanced atherosclerosis. 145 Moreover, in other small studies an association between FABP4 polymorphisms, plasma levels of FABP4 and metabolic outcome in polycystic ovary syndrome, 146 and obstructive sleep apnoea 147 have been found. Consequently, overwhelming biochemical and genetic evidence demonstrates an important correlation between circulating levels of FABP4 and metabolic disease, which raises the possibility that targeting this form of the molecule might be a useful therapeutic intervention.…”
Section: Circulating Fabp4 and Metabolic Pathologymentioning
confidence: 89%
“…Besides binding to long-chain fatty acids, FABP4 is also capable of binding to a variety of hydrophobic compounds, including cycloxygenases and oxidative products of fatty acids. It functions in both glucose and lipid metabolism [29, 30], and is involved in signal transduction [31], as well as in cell proliferation and apoptotic processes [32]. Its involvement in tumorigenesis has been investigated in bladder cancer [12], breast cancer [33, 34], ovarian cancer [35, 36], and oral squamous cell cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, data from both rodents and humans suggest that it is also secreted by adipose tissue into the bloodstream [13]. Recent studies have confirmed its roles in various conditions associated with insulin resistance, including MS, diabetes mellitus, nonalcoholic fatty liver disease, Cushing's syndrome, and polycystic ovary disease [14-18]. The aim of our study was to evaluate the correlations between A-FABP, systemic inflammation, and insulin resistance associated with critical illness, and further to investigate its role in outcome prediction.…”
Section: Introductionmentioning
confidence: 99%